2021
DOI: 10.1007/s00262-021-03083-3
|View full text |Cite
|
Sign up to set email alerts
|

Real-world outcomes of regorafenib combined with immune checkpoint inhibitors in patients with advanced or metastatic microsatellite stable colorectal cancer: A multicenter study

Abstract: Background Treatment strategies are limited for patients with chemotherapy refractory microsatellite stable (MSS) colorectal cancer. We aim to evaluate the efficacy and safety of immune checkpoint inhibitors (ICIs) combined with regorafenib in this population in routine clinical practice. Methods We retrospectively analyzed patients with advanced or metastatic colorectal cancer who received at least one dose of ICIs combined with regorafenib in 14 Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…39 patients who received regorafenib combined with toripalimab, with a median PFS of 2.6 months, a median OS of 15.5 months, and an ORR of 15.2% (24). Another multicenter retrospective study of regorafenib combined with immune checkpoint inhibitors included 84 mCRC patients, with an ORR of 5% and a median PFS of 3.1 months (25). Obviously, our results are similar to those of the appeal study in China.…”
Section: Discussionsupporting
confidence: 84%
“…39 patients who received regorafenib combined with toripalimab, with a median PFS of 2.6 months, a median OS of 15.5 months, and an ORR of 15.2% (24). Another multicenter retrospective study of regorafenib combined with immune checkpoint inhibitors included 84 mCRC patients, with an ORR of 5% and a median PFS of 3.1 months (25). Obviously, our results are similar to those of the appeal study in China.…”
Section: Discussionsupporting
confidence: 84%
“…The 3 references retrieved by citation were excluded because they were all from the same clinical trial and did not report detailed data on outcome indicators. Finally, 8 studies (14,30,31,(34)(35)(36)(37)(38) with a total of 1,287 patients were included in the metaanalysis (Table 1). The NOS scores of the included studies were all ≥7 (Table 2), indicating that the quality of the studies was good.…”
Section: Literature Search Results and Quality Evaluationmentioning
confidence: 99%
“… 5 However, several other studies evaluating the same treatment strategy failed to observe such a high response rate. 6 , 7 , 8 These discrepant observations suggest that only a subset of patients may benefit from this combination. Our findings suggest that regorafenib combined with a PD‐1 antibody has similar efficacy as regorafenib monotherapy in unselected MSS mCRC as a third‐line treatment option.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Yang et al conducted a study that involved 14 Chinese medical centers and reported a partial response of 5% (4/84 patients) and a median PFS of 3.1 months. 8 …”
Section: Introductionmentioning
confidence: 99%